2004
DOI: 10.1023/b:nere.0000035805.46592.6c
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Restraint Stress Alters Hippocampal Glutamate Uptake and Release in the Rat

Abstract: Glutamatergic mechanisms are thought to be involved in stress-induced changes of brain function, especially in the hippocampus. We hypothesized that alterations caused by the hormonal changes associated with chronic and acute stress may affect glutamate uptake and release from hippocampal synaptosomes in Wistar rats. It was found that [3H]glutamate uptake and release by hippocampal nerve endings, when measured 24 h after 1 h of acute restraint, presented no significant difference. The exposure to repeated rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…Thus, the excess of extracellular glutamate could be a feedback mechanism, as has been proposed between stress, glucose and glutamate in the brain, as glutamate stimulates the HPA axis promoting a continuous circle (Gabr et al, 1995). Interestingly, this change seems to be time-dependent and region-specific: after repeated stress (21-40 days), an increase in EAAT-2 has been found in hippocampus, which has been proposed as a counter-regulatory mechanism Fontella et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the excess of extracellular glutamate could be a feedback mechanism, as has been proposed between stress, glucose and glutamate in the brain, as glutamate stimulates the HPA axis promoting a continuous circle (Gabr et al, 1995). Interestingly, this change seems to be time-dependent and region-specific: after repeated stress (21-40 days), an increase in EAAT-2 has been found in hippocampus, which has been proposed as a counter-regulatory mechanism Fontella et al, 2004).…”
Section: Discussionmentioning
confidence: 91%
“…Since LTD is enhanced by stress and LTP is reduced (Xu et al, 1997), it has been suggested that stress may simply potentiate the system, saturating LTP, and thereby optimizing the conditions for inducing LTD. There is some evidence that stress can increase glutamate release within the hippocampus (Lowy et al, 1993;Stein-Behrens et al, 1994;Abraham et al, 1998;Fontella et al, 2004;Karst et al, 2005) that could lead to a general potentiation the system (Abraham et al, 1996). To determine if the altered synaptic plasticity following stress simply resulted from an increase in glutamate release during the stress period, we tried to temporarily potentiate the system by applying a 100 Hz tetanus prior to the application of the LFS.…”
Section: Discussionmentioning
confidence: 99%
“…Stress has been shown to increase glutamate release in CA1 (Stein-Behrens et al, 1994;Fontella et al, 2004), which may prime the system for the induction of LTD (Xu et al, 1997). To determine if excess glutamate contributes to LTD, a single pulse of 100 Hz was delivered to the Schaffer-collateral pathway 60 min prior to the administration of LFS to enhance extracellular glutamate concentration.…”
Section: Ampar Tyrosine Phosphorylation Is Required For Ltd Followingmentioning
confidence: 99%
“…Second, stress elevates extracellular glutamate level, thus facilitating glutamate signaling in the limbic brain. Chronic restraint stress, not acute stress, increases glutamate release and uptake in the hippocampus (Fontella et al, 2004;Lowy et al, 1993). Acute stress elevates extracellular glutamate level in the amygdala (Reznikov et al, 2007)and in the medial PFC (Moghaddam et al, 1994).…”
Section: The Protective Effect Of Lithium On Stress-induced Structuramentioning
confidence: 96%